Investigation on the Effect of Different Mild Acidic Electrolyte on ZIBs Electrode/Electrolyte Interface and the Performance Improvements With the Optimized Cathode - Gui, Yang; Lei, Yang; Fan, Bao An (Frontiers in Chemistry, 2020)
Zinc ion batteries (ZIBs), as promising alternatives of lithium ion batteries (LIBs), have aroused revived interest in the energy storage field recently. To obtain good performance, the choice of electrolyte plays a vital role. Therefore, in this work, three kinds of aqueous electrolyte have been assessed for interfacial effect and ZIB performance. Through the comparison, ZnSO4 electrolyte showed advantages on ionic conductivity over both Zn(NO3)2 and Zn(CH3COO)2 solution, Zn(CH3COO)2 exhibited considerable Zn stripping/plating kinetics with ZnSO4, and there was no characteristic peak pair of Zn dissolution/deposition found in Zn(NO3)2. Additionally, a lower charge transfer resistance was proved when the cell with 1 M ZnSO4 solution. Besides, to further study on cathodic graphite paper, activation and optimization has been conducted, and cells with optimized graphite paper showed an outstanding enhancement.